Design of Mental Disorder Consultation System with Decision Tree Method - Ahmad Sarif Hikmawan; Eko Prasetyo; Rifki Fahrial Zainal (JEECS (Journal of Electrical Engineering and Computer Sciences), 2019)
level or category of disorders suffered by patients, so patients can be dealt with quickly according to the level of the disorder they suffer. Diagnosing the level of mental disorders using the expert system will record the symptoms of the patient and will diagnose the level of the disorder based on the knowledge obtained from an expert, the mental disorder expert system uses the Decision Tree method. in general is a system that seeks to adopt human knowledge to computers, so that computers can solve problems as they are usually done by experts or before consulting a psychologist without reducing the expert role of the psychologist or in other words expert systems are systems that are designed and implemented with help certain programming languages to be able to solve problems as experts do quickly and efficiently. It is hoped that with this system, lay people can be more sensitive in recognizing the level of psychiatry in person. As for the experts of this system can be used as an assistant or supporting the performance of psychologist officers. Based on the results of the system tests that have been done, the accuracy of 97.5% results and system error 2.5% and the percentage of each diagnosis, 32% psychosis, 27% Neurosis, 17% Learning Soldered, 12% Juvenile Delinquency and Growth Flower 10%.